Staying mentally healthy: the biggest challenge faced during the COVID-19 pandemic, athletes` survey shows (2020)
A survey conducted by the International Olympic Committee (IOC) in May revealed that managing mental health and sports careers, as well as nutrition and diet, were the biggest challenges faced by athletes during the unprecedented time of the COVID-19 pandemic.